Leadership in Action : In Focus - Feedback and Development - The Negatives of Focusing Only on the Positive - Leslie, Jean Brittain (Center for Creative Leadership, 2005)
The approach of focusing only on developing strengths not only limits human potential but also may limit an organization's best performance to areas that are not the most important for the organization's future success.